oh gosh i cant belive how people here complicate a simple solution!!??
it is:
x2+3x-10=0
( x -2 ) ( x+5 )=0
X1= 2
x2= -5
There you have it. Hope it helped. Have a wonderful day. :))
2007-01-21 04:26:39
·
answer #1
·
answered by Jellyfish 3
·
0⤊
0⤋
once you should finish the sq. x^2 - 3x - 10 = 0 x^2 - 3x = 10 x^2 - 3x + (-3/2)^2 = 10 + (-3/2)^2 x^2 - 3x + 9/4 = 10 + 9/4 (x - 3/2)(x - 3/2) = 40 9/4 (x - 3/2)^2 = 40 9/4 x - 3/2 = ± ?(40 9/4) x - 3/2 = ± 7/2 x = (3 ± 7) / 2 x = {-2, 5} that is a lot extra reachable to component it x^2 - 3x - 10 = 0 (x + 2)(x - 5) = 0 x = {-2, 5}
2016-12-02 20:30:55
·
answer #2
·
answered by picart 4
·
0⤊
0⤋
x^2 + 3x - 10 = 0
First: factor the equation > multiply the 1st & 3rd coefficient to get "-10." Find two numbers that give you "-10" when multiplied & "3" (2nd/middle coefficient) when added/subtracted. The numbers are: 5 and -2 >>>
Sec: rewrite the expression with the new middle coefficients...
x^2 + 5x - 2x - 10 = 0
*When you have 4 terms - group "like" terms & factor...
(x^2 + 5x) - (2x - 10) = 0
x(x + 5) - 2(x + 5) = 0
(x + 5)(x - 2) = 0
Third: solve the two x-variables > place both sets of parenthesis to equal "0" >>>
1. x + 5 = 0
x+ 5 - 5 = 0 - 5
x = - 5
2. x - 2= 0
x - 2 + 2 = 0 + 2
x = 2
Soltuions: - 5 and 2
2007-01-21 04:14:21
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
=>
x=-5 or x=2
2007-01-21 04:16:47
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
You meant x^2 + 3x - 10 = 0. Use ^ for power.
You can use Bhaskara's formula: the solutions of ax^2 + bx + c = 0 are x = (-b +/- sqrt(b^2 - 4ac)) / (2a), provided that b^2 - 4ac >= 0.
Substituting the respective values into the formula:
x = ( -3 +/- sqrt(9 + 40) ) / (2 * 1) = (-3 +/- 7) / 2
Solution 1: x = (-3 + 7)/2 = 2
Solution 2: x = (-3 - 7)/2 = -5
2007-01-21 04:26:58
·
answer #5
·
answered by jcastro 6
·
0⤊
0⤋
x= -5 or 2
2007-01-21 04:13:30
·
answer #6
·
answered by rubydragon 2
·
0⤊
1⤋
you can put it into a binomial like...
x^2+3x-10=0 into (X+5)(x-2)=0 and then do..
X+5=0 take away 5 from both sides x=-5
and X-2=0 add 2 to both sides x=2
you could also use the quadratic formula if its not a perfect trinomial or use completing the square method to make a a perfect trinomial
i
2007-01-21 04:13:04
·
answer #7
·
answered by bob m 2
·
0⤊
1⤋
x^2 + 3x - 10 = 0
(x + 5)(x - 2) = 0
2007-01-21 04:13:41
·
answer #8
·
answered by Josh S 2
·
0⤊
1⤋
x^2 + 3x - 10 = 0
(x + 5)(x - 2) = 0
x = -5 or x = 2 are the two solutions
2007-01-21 04:10:01
·
answer #9
·
answered by JasonM 7
·
1⤊
2⤋
(x-2)(x+5)
x=-2 or 5
2007-01-21 04:42:57
·
answer #10
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋